2022
DOI: 10.1186/s12935-022-02743-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to overcome the main challenges of the use of exosomes as drug carrier for cancer therapy

Abstract: Exosomes are naturally occurring nanosized particles that aid intercellular communication by transmitting biological information between cells. Exosomes have therapeutic efficacy that can transfer their contents between cells as natural carriers. In addition, the exosomal contents delivered to the recipient pathological cells significantly inhibit cancer progression. However, exosome-based tumor treatments are inadequately precise or successful, and various challenges should be adequately overcome. Here, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 160 publications
0
68
0
Order By: Relevance
“…Thus, novel and specific mechanism-based drugs should be designed and synthesized for treating BC. Recent studies related to circRNA in cancer showed that circRNA could be used as a therapeutic strategy (Hussen et al, 2022;Wu et al, 2022).…”
Section: Exosomal Circrnas As Potential Therapeutic Targets In Breast...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, novel and specific mechanism-based drugs should be designed and synthesized for treating BC. Recent studies related to circRNA in cancer showed that circRNA could be used as a therapeutic strategy (Hussen et al, 2022;Wu et al, 2022).…”
Section: Exosomal Circrnas As Potential Therapeutic Targets In Breast...mentioning
confidence: 99%
“…Exosomes are nanometric vesicles of endosomal origin containing material from the host cell, such as proteins, lipids, DNA, and RNA (Hegmans et al, 2008). These vesicles are secreted by exocytosis and are taken up by other cells, influencing their functions and behavior, and can be used as a drug carrier for cancer therapy (Ghafouri-Fard et al, 2021a;Hussen et al, 2022). Tumorous cells use exosomes to communicate with their surroundings like other body cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although exosomes have been shown to possess invaluable qualities for use in nanomedicine, their low production rate in unaltered cell cultures remains a key challenge, preventing bench-to-bedside use. In addition to the low production of exosomes, large variability in their size also exists, resulting in a lack of reproducibility in batches [ 1 , 7 , 8 ]. Consequently, the need remains to develop techniques that increase exosome production, maintain constant morphology, and limit any negative impact on cell cultures.…”
Section: Exosomal Drug Delivery: Challengesmentioning
confidence: 99%
“…Bioactive cytokines, such as lipopolysaccharide (LPS) [ 62 ], N-methyldopamine [ 63 ], norepinephrine [ 63 ], serotonin [ 64 ], adiponectin [ 65 ], adenosine triphosphate (ATP) [ 66 ], Wnt3a [ 67 ], calcium (Ca 2+ ) ionophores [ 64 ], and plant ceramide [ 68 ] have been used in research to increase exosome production ( Table 3 ). Furthermore, the upregulation of NadB, syndecan 4, and six-transmembrane epithelial antigen of prostate 3 (STEAP3) has increased the exosomes produced in cell cultures [ 7 , 69 , 70 ]. Research has shown that the genetic overexpressions of tetraspanin CD9 and hypoxia-induced factor 1α (HIFα) have increased exosome production by 2.4- and 2.2-fold, respectively [ 71 , 72 , 73 ].…”
Section: Exosomal Drug Delivery: Solutionsmentioning
confidence: 99%
“…In this article, we delve into the promising applications of exosomes in drug delivery and personalized medicine, highlighting their potential and the challenges they present. [27][28][29]…”
Section: Roles Of Exosomes In Stem Cell Differentiation and Tissue Re...mentioning
confidence: 99%